2020
DOI: 10.21203/rs.3.rs-27670/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knockdown of hspg2 is associated with mandibular jaw joint fusion and neural crest cell dysfunction in zebrafish

Abstract: Background: Heparan sulfate proteoglycan 2 (HSPG2) encodes for perlecan, a large proteoglycan that plays an important role in cartilage formation, cell adhesion, and basement membrane stability. Mutations in HSPG2 have been associated with Schwartz-Jampel syndrome and Dyssegmental Dysplasia Silverman-Handmaker Type, two disorders characterized by skeletal abnormalities. These data indicate a function for HSPG2 in cartilage development/maintenance. However, the mechanisms in which HSPG2 regulates cartilage deve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
2
0
0
Order By: Relevance
“…Indeed, by quantifying the jaw joint expression of nkx3.2 in zebrafish embryos by measuring in situ hybridization staining intensity, we were able to measure a ~45% decrease at 48–56 hpf in homozygous JRS1 deletion mutants relative to wild types and heterozygous mutants. Castellanos and Quintana, 2021 reported mild jaw joint phenotypes reminiscent of those seen in our homozygous JRS1 mutants in 5 dpf hspg2 morphants that were associated with a ~30% reduction in nkx3.2 gene expression measured at 4 dpf. Their results and ours are consistent with earlier work indicating that a reduction in early nkx3.2 expression levels can result in more subtle jaw joint phenotypes, increasing in severity with increasing morpholino dosage ( Miller et al, 2003 ).…”
Section: Resultssupporting
confidence: 62%
“…Indeed, by quantifying the jaw joint expression of nkx3.2 in zebrafish embryos by measuring in situ hybridization staining intensity, we were able to measure a ~45% decrease at 48–56 hpf in homozygous JRS1 deletion mutants relative to wild types and heterozygous mutants. Castellanos and Quintana, 2021 reported mild jaw joint phenotypes reminiscent of those seen in our homozygous JRS1 mutants in 5 dpf hspg2 morphants that were associated with a ~30% reduction in nkx3.2 gene expression measured at 4 dpf. Their results and ours are consistent with earlier work indicating that a reduction in early nkx3.2 expression levels can result in more subtle jaw joint phenotypes, increasing in severity with increasing morpholino dosage ( Miller et al, 2003 ).…”
Section: Resultssupporting
confidence: 62%
“…It also indicates that JRS1 is most important to the early jaw joint expression of nkx3.2 , prior to 6 dpf, and may contribute relatively less to later expression. Castellanos et al (2021) recently reported subtle jaw joint phenotypes reminiscent of those seen in our homozygous JRS1 mutants in 5 dpf hspg2 morphants that were associated with a ∼30% reduction in nkx3.2 gene expression at 4 dpf. Their results and ours are consistent with earlier work indicating that a reduction in nkx3.2 expression levels can result in more subtle jaw joint phenotypes, increasing in severity with increasing morpholino dosage (Miller et al, 2003).…”
Section: Discussionsupporting
confidence: 62%